Pertanggungjawaban Notaris Terhadap Akta Yang Memuat Keterangan Palsu - Selvi Dhian Padma Sari (Officium Notarium, 2021)
This study raises the following issues: first, how is a notary responsible for the allegations of forgery in connection with the deed made? Second, what is the legal protection for a Notary accused of falsifying a deed? This study aims, firstly, to identify the responsibility of the Notary with the accusation of forgery in connection with the deed made. Second, to analyse the legal protection of a notary who is accused of falsifying a deed. This is a normative legal research, which uses primary legal materials, in the form of statutory regulations. Meanwhile, secondary legal materials are in the form of literature relevant to the object under study. This study uses a statutory approach and a conceptual approach. The analytical method used is normative law. This study concludes that first, the responsibility of the Notary to the deed made before them are civil liability, criminal liability, and administrative responsibility. Second, the form of legal protection is in the Criminal Code, as well as the form of legal protection from the Notary Honorary Council, and the form of legal protection from the Indonesian Notary Association (INI)Key Word: Notary, Accountability, Legal Protection AbstrakPenelitian ini mengangkat permasalahan: pertama, bagaimana pertanggungjawaban Notaris dengan adanya tuduhan pemalsuan sehubungan dengan akta yang dibuat? Kedua, Bagaimana perlindungan hukum terhadap Notaris yang dituduh memalsukan akta? Penelitian ini bertujuan, pertama, untuk mengetahui tanggung jawab Notaris dengan adanya tuduhan pemalsuan sehubungan dengan akta yang dibuat. Kedua, Untuk mengetahui perlindungan hukum terhadap Notaris yang dituduh memalsukan akta. Penelitian ini adalah penelitian hukum normatif, yang menggunakan bahan hukum primer, berupa peraturan perundang-undangan. Sedangkan bahan hukum sekunder berupa literatur yang relevan dengan obyek yang diteliti. Penelitian ini menggunakan pedekatan perundang-undangan (statute approach) dan pendekatan konsep (conseptual approach). Metode analisis yang digunakan adalah hukum normatif. Penelitian ini menyimpulkan, pertama, tanggung jawab Notaris terhadap akta yang dibuat dihadapanya yaitu pertanggungjawaban secara perdata, pertanggungjawaban secara pidana, dan pertanggungjawaban secara administraitif. Kedua, bentuk perlindungan hukum yaitu dalam KUHPidana, serta bentuk perlindungan hukum dari Majelis Kehormatan Notaris, dan bentuk perlindungan hukum dari Ikatan Notaris Indonesia (INI).Kata-kata Kunci: Notaris, Pertanggungjawaban, Perlindungan Hukum